The Problem of Intersubjectivity in the Theories of E. Husserl and A. Schütz - Žiemytė, Rasa (Problemos, 1997)
The article is concerned with the problem of intersubjective understanding in the theories of E. Husserl and A. Schütz. While analyzing the meanings of the concept of Lebenswelt in phenomenological philosophy and Schütz’s sociology, different positions regarding the problem are revealed; therefore, these positions have the same point of departure, an emphatical understanding of Other, which is considered an obstacle for the phenomenological explanation of mutual understanding. Both conceptions of intersubjectivity, especially Husserl’s, lack the aspect of linguistic communication which would resolve conceptual problems arising in the theories of intersubjective understanding.